Pelatihan dan Penyuluhan Tentang Pengolahan Sampah Organik dan Anorganik Berbasis Zero Waste - Chika Raichany Tama; Husnul Khatimah; Purnama Putra (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2023)
This community service activity aims to obtain alternative natural products as cleaning fluids, disinfectants, and to reduce plastic waste, as well as recycle it using plastic bottles to make something useful during the COVID-19 pandemic and reduce the impact of environmental pollution. The method of implementation begins with collecting data and information, coordinating with the head of RT12 in self-help gang 3 and with mothers in self-help gang 3, the preparation stage and training activities for mothers in self-help gang 3. Innovation and creativity in making eco-enzymes and ecobrick, is present as the best solution for housewives in processing organic and inorganic waste into something more useful. The housewives have new activities, can save more expenses and indirectly help the cleaners in sorting household waste into organic and inorganic waste. Through this activity, it is hoped that housewives can be more creative and innovative in processing household waste in the future.